Sally Jean, the Bicycle Queen - Best, Cari.; Davenier, Christine (New York : Farrar, Straus and Giroux, 2006)
When Sally Jean outgrows her beloved bicycle, Flash, she experiments with various ideas for acquiring a new, bigger one.
"Melanie Kroupa books.".
Parents' Choice, January 2006.
Wilson's Children, October 2010.
School Library Journal starred, May 2006.
Publisher's Weekly, June 2006.
Booklist, May 2006.
Keywords: Bicycles -- Juvenile fiction; Fund raising -- Juvenile fiction; Self-reliance -- Juvenile fiction; Growth -- Juvenile fiction; Bicycles and bicycling -- Fiction; Moneymaking projects -- Fiction; Self-reliance -- Fiction; Growth -- Fiction; Bicycles -- Fiction; Money-making projects for children -- Fiction; Self-reliance -- Fiction; Growth -- Fiction; Bicycles and bicycling -- Fiction; Moneymaking projects -- Fiction; Self-reliance -- Fiction